Naturally Acquired Picornavirus Infections in Primates at the Dhaka Zoo - Oberste, M. Steven (American Society for Microbiology, 2013)
The conditions in densely populated Bangladesh favor picornavirus transmission, resulting in a high rate of infection in the human population. Data suggest that nonhuman primates (NHP) may play a role in the maintenance and transmission of diverse picornaviruses in Bangladesh. At the Dhaka Zoo, multiple NHP species are caged in close proximity. Their proximity to other species and to humans, both zoo workers and visitors, provides the potential for cross-species transmission. To investigate possible interspecies and intraspecies transmission of picornaviruses among NHP, we collected fecal specimens from nine NHP taxa at the Dhaka Zoo at three time points, August 2007, January 2008, and June 2008. Specimens were screened using real-time PCR for the genera Enterovirus, Parechovirus, and Sapelovirus, and positive samples were typed by VP1 sequencing. Fifty-two picornaviruses comprising 10 distinct serotypes were detected in 83 fecal samples. Four of these serotypes, simian virus 19 (SV19), baboon enterovirus (BaEV), enterovirus 112 (EV112), and EV115, have been solely associated with infection in NHP. EV112, EV115, and SV19 accounted for 88% of all picornaviruses detected. Over 80% of samples from cages housing rhesus macaques, olive baboons, or hamadryas baboons were positive for a picornavirus, while no picornaviruses were detected in samples from capped langurs or vervet monkeys. In contrast to our findings among synanthropic NHP in Bangladesh where 100% of the picornaviruses detected were of human serotypes, in the zoo population, only 15% of picornaviruses detected in NHP were of human origin. Specific serotypes tended to persist over time, suggesting either persistent infection of individuals or cycles of reinfection.